2019
DOI: 10.1177/2054358119877405
|View full text |Cite
|
Sign up to set email alerts
|

Provincial Needs Assessment to Determine the Current State of Glomerulonephritis Care in Ontario

Abstract: Background: Despite its relative rarity, glomerulonephritis (GN) accounts for 20% of prevalent end-stage renal disease patients in Ontario. Early identification and appropriate management of GN to delay progression of disease can reduce patient morbidity and health system costs. As such, a provincial GN needs assessment was conducted to inform on the development of the provincial GN strategic framework in Ontario. Objective: To understand the current state of GN care in Ontario from nephrologist, hospital admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…People with GN recognize holistic care as being important—in Ontario, 84% of people with GN ranked access to specialized, multidisciplinary care as very important or important, while 81% ranked education, counseling and support for patients and families as being very important or important. 5 These findings informed the development of a government-sponsored program in Ontario, that includes 6 GN specialty clinics fully staffed by nurses, pharmacists, social workers, pathologists, and nephrologists. While specialized clinics can enhance the level of support available for people with GN, there remains a lack of research or guidelines in GN to inform interventions that directly target life participation, fatigue, or other priority PROs.…”
Section: Patient-reported Outcomes (Proms)mentioning
confidence: 96%
See 3 more Smart Citations
“…People with GN recognize holistic care as being important—in Ontario, 84% of people with GN ranked access to specialized, multidisciplinary care as very important or important, while 81% ranked education, counseling and support for patients and families as being very important or important. 5 These findings informed the development of a government-sponsored program in Ontario, that includes 6 GN specialty clinics fully staffed by nurses, pharmacists, social workers, pathologists, and nephrologists. While specialized clinics can enhance the level of support available for people with GN, there remains a lack of research or guidelines in GN to inform interventions that directly target life participation, fatigue, or other priority PROs.…”
Section: Patient-reported Outcomes (Proms)mentioning
confidence: 96%
“…Challenges may occur at multiple stages in the care of patients living with GN, which may begin with delays in referral to nephrology, precipitating potential downstream consequences. 5 This was the case of our patient partner Kate who stated that there were some “hiccups” in her journey including being diagnosed quite late with IgAN at which point she had advanced chronic kidney disease (CKD). In a cross-sectional study from Ontario, 40% of patients living with GN reported delayed diagnosis and 45% were diagnosed after progression to advanced kidney disease nearing ESKD.…”
Section: Diagnosis Of Glomerulonephritis and Novel Biomarkers And Ant...mentioning
confidence: 99%
See 2 more Smart Citations
“…Stakeholder surveys previously conducted by ORN identified that both clinicians and patients do not perceive access to drugs to treat GN as comprehensive or timely. 17 To inform initiatives on improving access, ORN undertook a jurisdictional scan to examine current access, extent of public coverage, and timelines for public coverage in Canadian provinces for adults who are prescribed IS agents for GN.…”
Section: Program Description and Objectivesmentioning
confidence: 99%